Emerging Issues in Occupational Health Psychology - León-Pérez, Jose M.; Shoss, Mindy K.; Ferreira, Aristides I.; Giorgi, Gabriele (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book compiles the cutting-edge research published in the Special Issue "Emerging Issues in Occupational Health Psychology" (International Journal of Environmental Research and Public Health). The articles included in this book use strong and innovative theoretical approaches to provide evidence regarding the importance of working characteristics and resources to promote healthier and more sustainable environments in which employees can be happy and productive.